Immunocytochemical Characterization of Alzheimer's Disease Hallmarks in APP/PS1 Transgenic Mice Treated with a New Anti-Amyloid-β Vaccine - Ivan Carrera; Ignacio Etcheverria; Yi Li; Lucia Fernandez-Novoa; Valter Lombardi; Carmen Vigo; Hector H. Palacios; Valery V. Benberin; Ramon Cacabelos; Gjumrakch Aliev (University Library System, University of Pittsburgh, 2014)
Introduction: APP/PS1 double-transgenic mouse models of Alzheimer's disease (AD), which overexpress mutated forms of the gene for the human amyloid precursor protein (APP) and presenilin 1 (PS1), have provided robust neuropathological hallmarks of an AD-like pattern at early ages. This study aimed to characterize immunocytochemical patterns of the AD mouse brain, which is treated with the EB101 vaccine, as a model for human AD. Material and methods: In this novel vaccine, a new approach has been taken to circumvent past failures with Aβ vaccines by judiciously selecting an adjuvant consisting of a physiological matrix embedded in liposomes, composed of naturally occurring phospholipids (phosphatidylcholine, phosphatidylglycerol, and cholesterol). Results: Our findings showed that the administration of amyloid-β1−42 (Aβ) and sphingosine-1-phosphate emulsified in liposome complex (EB101) to APP/PS1 mice before the onset of Aβ brain deposition (at 7 weeks of age) and/or at an older age (35 weeks of age) can be effective in both halting the progression and clearing the AD-like neuropathological hallmarks. In addition, passive immunization with EB101 did not activate inflammatory responses from the immune system and astrocytes. Consistent with a decreased inflammatory background, the basal immunological interaction between the T cells and the affected areas (hippocampus) in the brain of treated mice was notably reduced. Conclusion: These results provide strong evidence that immunization with the EB101 vaccine prevents and attenuates AD neuropathology in this type of double-transgenic mice.